2003
DOI: 10.1152/ajpcell.00041.2003
|View full text |Cite
|
Sign up to set email alerts
|

More than apical: distribution of SGLT1 in Caco-2 cells

Abstract: We investigated the distribution of the endogenous sodium-d-glucose cotransporter (SGLT1) in polarized Caco-2 cells, a model for enterocytes. A cellular organelle fraction was separated by free-flow electrophoresis and subjected to the analysis of endogenous and exogenous marker enzymes for various membrane vesicle components. Furthermore, the presence of SGLT1 was tested by an ELISA assay employing newly developed epitope specific antibodies. Thereby it was found that the major amount of SGLT1 resided in intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 47 publications
12
51
1
1
Order By: Relevance
“…Stainings of SGLT-1 on the cell surface as well as in cytoplasmic pools were observed in control cells. This observation is consistent with previously described intracellular pools containing SGLT-1 in enterocytes ( [Chung et al, 2002a], [Chung et al, 2002b] and [Kipp et al, 2003]). Our findings indicate that the increased SGLT-1-specific sugar uptake triggered by exposure to G. duodenalis resulted from an augmentation of V max of the cotransporter, without changes in K m. These data indicate that G. duodenalis increased the maximal rate of SGLT-1 sugar transport (increased surface expression of transporter), whereas the affinity between the transporter and ligand was not altered.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Stainings of SGLT-1 on the cell surface as well as in cytoplasmic pools were observed in control cells. This observation is consistent with previously described intracellular pools containing SGLT-1 in enterocytes ( [Chung et al, 2002a], [Chung et al, 2002b] and [Kipp et al, 2003]). Our findings indicate that the increased SGLT-1-specific sugar uptake triggered by exposure to G. duodenalis resulted from an augmentation of V max of the cotransporter, without changes in K m. These data indicate that G. duodenalis increased the maximal rate of SGLT-1 sugar transport (increased surface expression of transporter), whereas the affinity between the transporter and ligand was not altered.…”
Section: Discussionsupporting
confidence: 94%
“…Additional Western blot results showed that the total amount of SGLT-1 protein in epithelial cells was not increased postchallenge, suggesting that novel synthesis of the protein may not be involved in this phenomenon. Further evidence indicated that the increased expression of SGLT-1 on apical membranes of enterocytes requires intact cytoskeletal proteins and microtubules, in agreement with previous reports suggesting that intracellular compartments containing SGLT-1 are attached to microtubules (Kipp et al, 2003). In contrast, as cytochalasin D had no effect on SGLT-1 activation, actin filaments do not appear to be involved in this process.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We demonstrated that antibodies against these regions coupled separately to AFM tips could interact specifically with the antigenic-binding epitopes of SGLT1. These results confirm the extracellular orientations of the regions of the subdomain I (aa 243-272), II (aa 339 -356), and III (aa 606 -630), which support the assumptions derived from previous studies (5-8, 33) and also from our immunohistochemistry labeling the surface of SGLT1-expressing cells (26). Furthermore, the binding probabilities of the three antibodies to SGLT1 are quite similar.…”
Section: Discussionsupporting
confidence: 90%
“…Immunopurified polyclonal antibodies QIS30 (subdomain I), PAN2-2 (subdomain II), and PAN3-2 (subdomain III) were raised against oligopeptides from the amino acid sequences aa 243-272 (loop 6 -7, i.e. the loop between the transmembrane helices 6 and 7), aa 339 -356 (loop 8 -9), and aa 606 -630 (loop 13-14) of rbSGLT1 (rabbit isoform), respectively, as described before (6,25,26). The specificity of the interaction of the antibodies with the supposed epitopes has been shown in independent previous immunohistochemistry studies where surface labeling of the cells could be prevented in the presence of the peptides used for their generation.…”
Section: Methodsmentioning
confidence: 99%